Influence of Competence, Transparency and Accountability on Income and Expenditure Budget Management Village (APBDes) - Husaen, Ade (Entrepreneurship and Small Business Research, 2022)
This study aims to determine (1) the effect of competence on the management of village income and expenditure budgets (APBDes) (2) The effect of transparency on the management of village income and expenditure budgets (APBDes) (3) The effect of accountability on village income and expenditure budget management (APBDes). This research was carried out in a village in the Malifut sub-district, North Halmahera district. With a total population of 88 respondents. The sampling technique used a purposive sampling technique with a sample of 22 villages in the Malifut sub-district. The type of data used in this study is the type of quantitative data while the data source is the primary data source. The method of data collection is done by using a questionnaire. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that (1) Competence has a significant effect on the management of village income and expenditure budgets in the Malifut sub-district. (2) Transparency has a significant effect on the management of village revenue and expenditure budgets in the Malifut sub-district. (3) Accountability has a significant effect on the management of the village income and expenditure budget in the Malifut sub-district.